Manufacturing Ketchup with New Sensory Specifications and Studying the Consumer Acceptance of It (Latakia University Journal -Biological Sciences Series, 2023)
The ketchup industry is one of the most important food industries in the world. This industry has witnessed a great development with the aim of manufacturing ketchup with new sensory specifications. , 4% coriander, 2% cloves, 4% cloves, (1)% cloves + 1% coriander), (2% cloves + 2% coriander)) and we performed 63 manufacturing processes, the results of the questionnaire showed that coriander changed the taste and smell of ketchup and was accepted by tasters at low percentages, and in terms of color, the lowest value of the average color evaluation values ​​for samples of sweet ketchup was 4% cloves, and the texture was affected by the addition of spices, especially at high percentages of addition, as for general acceptance Through the study, it was found that the lower percentage of addition of spices had the highest acceptance, The drip acidity test was carried out, and the values ​​ranged from (0.05 ± 0.21: 0.05 ± 0.36), and the pH test, and the values ​​ranged from (5: (5.5), and the general census test for yeasts and fungi, and the values ​​ranged from (0.08 ± 4.7: 0.13 ± 5.75).